Association of dietary inflammatory index with chronic kidney disease and kidney stones in Iranian adults: A cross-sectional study within the Ravansar non-communicable diseases cohort - Moludi, Jalal; Fateh, Hawal Lateef; Pasdar, Yahya; Moradinazar, Mehdi; Sheikhi, Leila; Saber, Amir; Kamari, Negin; Bonyani, Mitra; Najafi, Farid; Dey, Priyankar (Frontiers in Nutrition, 2022)
Chronic inflammation plays central role in the pathogenesis of chronic kidney disease (CKD). The association of dietary inflammatory index (DII) with CKD is remains underexplored. Thus, the present study aimed to determine the association between the DII, risk of CKD, and kidney stones formation using the data from the Ravansar Non-Communicable Diseases (RaNCD) cohort study conducted in Kermanshah, Iran. The cross-sectional study was conducted using the recruitment phase data of the RaNCD cohort study comprising of 9824 individuals with an age range of 35 - 65 y. Food frequency questionnaires (FFQ) were used to evaluate the association between the diet and DII scores. Renal function was assessed using estimated glomerular filtration rate (eGFR), blood urea nitrogen (BUN), and serum creatinine (Cr) level. CKD was defined based on eGFR. The prevalence of kidney stones was evaluated by participants' self-report. A total of 1,791 participants (18.24%) had kidney stones, while a majority were in the first quartile (27.69%). Out of 9824 subjects 1,747 subjects (eGFR: 18.50 ml/min per 1.73 m2; 95% confidence interval (CI): 17.72–19.30) had CKD. A significant trend for eGFR across all quartiles (Qs) of DII was observed. The odds ratio of CKD in the fourth quartile (pro-inflammatory diet) was 4.38-times higher than in the first quartile (anti-inflammatory diet) of DII (95% CI = 3.58 - 5.36). Women were found to be more likely to have less eGFR than men in the DII Qs. Collectively, the findings indicated that consumption of pro-inflammatory diet was associated with a high occurrence of CKD. Interestingly, the results also revealed that a pro-inflammatory diet had no significant correlation with kidney stone development.